The Influence of Microfungi on the Mycelial Growth of Ectomycorrhizal Fungus Tricholoma matsutake - Seung-Yoon Oh; Myung Soo Park; Young Woon Lim (Microorganisms, 2019)
Pine mushroom (Tricholoma matsutake) is one of the most valued ectomycorrhizal fungi in Asia because of its unique pine-like aroma; however, due to exceptionally slow growth of its mycelia in artificial conditions, its cultivation has been largely deemed as not possible. Previous studies have shown that some bacteria and a few Trichoderma species associated with pine mushroom promoted the growth of T. matsutake isolate, but this effect is relatively unexplored. In this study, we investigated the diversity of microfungi in the fairy ring of T. matsutake and their effect on the growth of T. matsutake isolate. From 184 fungal isolates, 28 species were identified based on suitable molecular markers. Penicillium was most frequently observed (16 species), followed by Trichoderma (4 species). Five Zygomycota species showed a high promoting effect on the growth of T. matsutake while the effects of ascomycetes were mixed. The microfungi that promote the growth of T. matsutake can be useful for forest nursery and artificial cultivation of T. matsutake.